POGIL, Guided, and Free Inquiry: Which Model Best Enhances Students' Critical Thinking in Biology Learning? - Wiwik, Wiwik; Adnan, Adnan; Ali, Alimuddin (Jurnal Pendidikan MIPA, 2025)
This study aims to determine the effect of inquiry-based learning models (POGIL, guided inquiry, and free inquiry) on improving students' critical thinking skills in biology. Biology learning requires high-level thinking skills, one of which is critical thinking, which must be developed through effective learning strategies. This study uses a quantitative approach with a quasi-experimental design. The study population consists of all eleventh-grade students at State High School 9, Makassar. The sample comprises 130 students, distributed across four classes: three experimental classes that implement inquiry-based learning models and one control class using the STAD learning model. The topic used in this study is the respiratory system. The instrument used was a critical thinking skills test administered before and after the treatment (pretest and posttest). Data analysis was conducted using Analysis of Covariance (ANCOVA) to determine the effect of the treatment, followed by the Least Significant Difference (LSD) test to identify significant differences between groups. The results of the study showed that there were significant differences in the improvement of critical thinking skills between the four models based on the ANCOVA test with a significance value of less than 0.05. The LSD test results showed that POGIL was superior to guided inquiry, free inquiry, and STAD. Meanwhile, guided inquiry and free inquiry did not show any differences, and STAD, as the control class, showed the lowest effect. In biology education, teachers should consider implementing the POGIL learning model as an alternative learning strategy to develop students' critical thinking skills. Teachers can also vary the use of inquiry models according to student characteristics and lesson content, and optimize the role of collaborative learning to enhance learning outcomes.   Keywords: POGIL, guided inquiry, free inquiry, critical thinking skills, STAD.